Demographics, fiscal health, and school quality: shedding light on school closure decisions - Sherrilyn M. Billger (Institute for the Study of Labor (IZA), 2010)
In our current challenging budgetary environment, school closures remain a potentially attractive choice. With a large panel of Illinois schools from 1991 to 2005, I investigate which factors contribute to school closures. Among elementary schools, declining enrolments and rural locations coincide with closures. However, schools with higher per-pupil spending are ceteris paribus less likely to close. Furthermore, better test scores also yield lower probabilities. High expenditures contribute to junior high closure, but the most significant predictors are the proportions of black and low income students. Administrators may claim that low enrolments and high spending motivate school closures, but in Illinois, that is not the whole story.
Keywords: I22; I28; H75; 330; Education finance; education administration; school closures; tax policy; Allgemeinbildende Schule; Liquidation; Schulfinanzierung; Bildungsverhalten; Bildungsökonomik; Schätzung; Illinois